THE RELATIONSHIP BETWEEN RISKS OF OBSTRUCTIVE SLEEP APNEA AND DRY EYE DISEASE - Aldina, Rosy; Yanuar, Ferdian; Afif, Zamroni; Holipah; Prayitnaningsih, Seskoati (MNJ (Malang Neurology Journal), 2024)
Introduction: Dry Eye Disease (DED) may lead to decreased visual function, chronic tissue changes, eyelid, conjunctival, and corneal abnormality. The prevalence of DED in Asia ranges from 21.6%–37.6%. Several studies pointed out the relationship between DED and Obstructive Sleep Apnea (OSA). In patients with OSA, oxidative stress, hypoxia, and ocular surface inflammation increase, leading to a decrease in the functions of meibomian glands, goblet cells, corneal sensitivity, and tear production as a response to the stimulations from the lacrimal glands. The loss of conjunctival goblet cells and meibomian glands are implications of damage to the tear film quality, which results in DED. Method: This is a population-based cross-sectional study. Data were obtained from the database of Biomarker Smarthealth Research in Mendalanwangi, Sidorahayu, and Cepokomulyo Villages, which are located in Malang Regency, having risks of OSA (based on the STOP-BANG questionnaire), above ≥40 years old, and DED Examination with Tear Break-Up Time (TBUT), MGD (Meibominan Gland Dysfunction), Tear Meniscus (TM) involving a total of 518 respondents. The available data were then processed according to the variables and went through DED examinations. This study employed the purposive sampling method. Result: In this study, moderate risk of OSA suggests a significant influence on the occurrence of DED with an odds ratio (OR) 1.66 (p<0.05). In addition, moderate risk of OSA predisposes ADDE (Aqueous Deficiency Dry Eye)-type and Mix-type DED with OR 2.85 and 1.23 (p<0.05). High risk of OSA correlates with the occurrence of ADDE-type DED with OR 2.37 (p<0.05). The age group >60 years old shows a correlation with Mix-type DED with OR 2.09 (p<0.05). Women have a higher predisposition to ADDE-type with OR 2.58 (p<0.05). Conclusion: Moderate risk of OSA influences the occurrence of DED, both ADDE-type and Mix type; whereas high risk of OSA only correlates with ADDE-type. Older age plays a role in the occurrence of Mix-type DED and women have a higher tendency to present with ADDE- type.